Język polski: English - Waściński, Tadeusz (Management and Administration Journal, 2021)
The material presented discusses the issues of financial analysis to monitor the position of the company from the competition. Managing a business is a constant, complex process of making and implementing decisions affected by a high degree of risk. In the face of increasing market saturation and the temperature on the increased competition, the value of information resulting from the ratio analysis is a strategic resource, allowing to minimize the impact of risk on decisions. What greatly increases the likelihood of achieving economic success. The main objective of the study is to assess the economic processes and economic and identification of cause - effect relationships that are formed between certain categories of financial - economic in the construction industry. The purpose of this analysis is to determine whether and to what extent changes in the achieved financial results have been obtained as a result of economic activity, and how stable is the company’s position X on the market.